Reducing lane width for Singapore roads - Tan, Guan You (2018)
Due to the significant of influx of foreigners, increase in vehicle population, and scarcity of land in Singapore, much strain is created on the transport infrastructures of Singapore. Also, with increasing number of cyclists in recent years, Singapore faces a new challenge given the land scarcity. Some questions asked are: How do we incorporate efficient land usage for cyclists in Singapore? How do we ensure the co-existence of cyclist and motorist on-road? This study is to provide solutions by reducing lane width on major arterial road and expressway to incorporate sufficient land space for constructing a cycling path for cyclists. Driving behaviour and the effect on driving speed on road with different lane width sizes in different traffic scenarios are studied through a driving simulator. The experiment covered the current Singapore arterial roads and expressways such as Thomson Road, Lornie Road and PIE (Pan Island Expressway). The usage of driving simulator could facilitate in examining the plausible results in real-life driving before investing heavily on constructing on-road facilities for cyclist on-road. The study covered 122 participants according to their age namely: young adults, middle-aged adults and senior citizen. The trend shows that with age, the driving speed shows a significant reduction. The reduction in lane width also causes the reduction in driving speed for older drivers probably due to slower reaction time and greater wariness of the surrounding. Some of the notable issues that affect the driving speed and driving behaviour on road are influenced by roadside vegetation, and positioning of rear and side mirrors. The study found out that narrow lane width cause reduction in speed due to perception of a higher perceived risks on the road such as colliding with surrounding vehicles, and collision onto nearby road facilities. For future consideration and references, reduction of lane width causes vehicles’ overall operating speed to drop, and it also helps to save land spaces for construction of on-road facilities. In this case, there will be sufficient space for cycling lane and on-road vehicles that would be driving at a lower speed with a reduction of lane width.